PENGARUH SIMPANAN ANGGOTA TERHADAP MODAL PADA KOPERASI “SUMBER BAHAGIA” KOTA MADIUN TAHUN 2007-2011 - Maretha Berlianantiya (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
This research aims to find out the member savings influence which consist of basic savings, obligation savings, voluntarily savings, and Housing Credit Unit (HCU) savings to financial capital which come from basic savings, obligation saving plus voluntarily savings which has added savings of (HCU), reserve fund, donation and Residu of Trade Outcome (RTO) which is not divided and that has added tax, fluent obligatory and long-term obligatory in Sumber Bahagia Cooperation Madiun year 2007-2011. The determiniation of sample I this research uses all population member as sample. The population in this research is all savings and financial capital Sumber Bahagia Cooperation during 5 years, from 2007 up to 2011 and the sample in this research is all savings and financial capital in Sumber Bahagia Coorperation during 5 years, from 2007 up to 2011. Data collecting uses interview method and documentation. In analizing data, researcher using correlation formula of Kendall Tau. Result shows that member savings has the influence and positive relationship toward financial capital in Sumber Bahagia Cooperation Madiun. It is found from the table score for S =10, N = 5 is 0,0083 and counting of correlation formula of Kendall Tau is 1. It means that table critical value (1.0,0083). This result indicates that Ho rejected. It means that there is an influence among member savings toward financial capital in Sumber Bahagia Cooperation Madiun year 2007-2011.